IMPLEMENTATION OF THE PRINCIPLE OF EQUALITY OF PARENTAL RIGHTS AND RESPONSIBILITIES - Aitniyazova Sayora Parakhatovna (Scholar Express Journals, 2023)
The concepts of "equality" and "equality" are often used as equivalent terms in the legal literature. Some scholars believe that "subjective rights and responsibilities in the parental relationship merge together", parental rights are also parental responsibilities at the same time.
Keywords: Legal; Democratic; parental